Web Quality Analysis (ui/UX) in the marketplace using a Technology Acceptance Model (TAM) approach - Alwi Nur Hafidz; Arfhan Prasetyo; Mugi Raharjo (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
In January 2021, the number of internet users in Indonesia was 202.6 million. Business people or companies should use opportunities like this to gain more profits. The role of e-commerce also needs to be maximized in improving the country's economy. However, increased consumer satisfaction and purchasing decisions in using the marketplace. Of course, it was affected by several things. Based on this description, the author is interested in conducting further research on the effect of UI and UX on the marketplace in Indonesia in impacting consumer purchasing decisions. The author uses the technology acceptance model method to measure the perceived usefulness and perceived ease of use as independent variables on the behavioural intention to use as the dependent variable. It expected that the result of this research could be able to see how impactful is UI/UX on consumer purchasing decisions.